PENGARUH RELATIONSHIP MARKETING DAN KUALITAS LAYANAN TERHADAP KEPUASAN DAN LOYALITAS NASABAH - Ubaidillah Ubaidillah (Jurnal Bisnis dan Manajemen, 2017)
Banking challenges in today's global competition directly sue the effectiveness of marketing strategies as a form of efforts to preserve and develop competitive advantage of a company, it can be achieved by one through Relationship Marketing strategies. The purpose of this study were (1) To analyze the direct effect of relationship marketing on customer loyalty. (2) To analyze the influence of Quality of Service directly on customer loyalty. (3) To analyze the effect of relationship marketing on customer loyalty through customer satisfaction. This research uses explanatory research type. The population in this study are customers who have become customers of funding of at least 1 year and has accounts that are still active status. sample used was 150 respondents. The instruments used in data collection was the questionnaire. The analysis technique used in this research is Structural Equation Modelling (SEM) using AMOS program. The results of this study show that Relationship Marketing has a direct influence on customer loyalty. Better service quality can increase customer loyalty funding. Relationship Marketing has an indirect effect on customer loyalty through customer satisfaction. Quality of service is a positive effect on customer loyalty through customer satisfaction. DOI : https://doi.org/10.26905/jbm.v4i1.1716